2015
DOI: 10.17795/jjnpp-17255
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I Converting Enzyme Inhibitory Activities of Hydroalcoholic Extract of Nardostachys jatamansi, Prangos ferulacea and Marrubium vulgare

Abstract: Background: Hypertension is one of the major risk factors for cardiovascular diseases. Lifestyle changes, physical exercise and intake of healthy diet are some common issues associated with reducing the risk of hypertension. There are several classes of pharmacological agents used in the treatment of hypertension. Angiotensin I converting enzyme (ACE) cleaves angiotensin I to angiotensin II and inactivates bradykinin. The synthetic ACE inhibitors are used widely to treat cardiovascular disorders. They may caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…IC50 values of these plants were found as 2.147 mg mL -1 , 4.057 mg mL -1 and 0.791 mg mL -1 , respectively. The minimum value of IC50 was M. Vulgare (Namjoyan et al, 2015). In our study IC50 values for water and butanol extracts of Thymbra sintenisii plant were found as 1.696 mg mL -1 and 0.395 mg mL -1 , respectively According to our study, inhibitory impact of water and butanol extracts of Thymbra sintenisii is more than their plants extracts.…”
Section: Resultssupporting
confidence: 48%
“…IC50 values of these plants were found as 2.147 mg mL -1 , 4.057 mg mL -1 and 0.791 mg mL -1 , respectively. The minimum value of IC50 was M. Vulgare (Namjoyan et al, 2015). In our study IC50 values for water and butanol extracts of Thymbra sintenisii plant were found as 1.696 mg mL -1 and 0.395 mg mL -1 , respectively According to our study, inhibitory impact of water and butanol extracts of Thymbra sintenisii is more than their plants extracts.…”
Section: Resultssupporting
confidence: 48%
“…In the literature, there are a number of papers promising about phytochemical properties and biological activities of diverse Marrubium species (7,(11)(12)(13)(14)(15)(16)(17)(18)(19). However, there is no information about phytochemistry and biological potent of endemic species M. sivasense.…”
Section: Resultsmentioning
confidence: 99%
“…A previous phytochemical studies on Marrubium species resulted with polyphenols (7), essential oils (8), labdane diterpenoids and sterols (9,10). Biological activity investigations of Marrubium species encompasses antibacterial (11), antioxidant, antiproliferative (12), antinociceptive (13), antidiabetic (14), antihypertensive (15), hepatoprotective (16), antiinflammatory (17), cardioprotective (18) and cytotoxic/cytostatic (19) potentials. Some Marrubium species are traditionally used to treat various diseases, including asthma, pulmonary infections, inflammation and hypotension, as cholagogues and sedative agents, and for pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…The angiotensin converting enzyme (ACE) inhibitory activity of different P. asperula extracts was tested in vitro, and only the n-hexane fraction was found to be active with an IC 50 of 0.150 mg/mL (Loizzo et al 2008a). The hydroalcoholic extract of P. ferulacea exhibited a weak inhibition of ACE with IC 50 value of 4.057 mg/mL (Namjoyan et al 2015).…”
Section: Anti-hypertensive Effectmentioning
confidence: 98%
“…The most commonly used species of this genus are P. ferulacea and P. pabularia. The leaves of these plants are traditionally used as laxative, antihypertensive, and carminative agents and are also recommended for the treatment of digestive disorders (Dokovic et al 2004;Sagun et al 2006;Kazerooni et al 2006;Durmaz et al 2006;Ö zek et al 2007;Ahmed et al 2011a;Razavi 2012b;Farooq et al 2014a;Shokoohinia et al 2014;Namjoyan et al 2015;Seidi Damyeh et al 2016;Tabanca et al 2016;Gheisari et al 2016;Yousefi et al 2017;Delnavazi et al 2017;Kiliç et al 2017;Ozek et al 2018;Sadeghi and Bazdar 2018;Abbas-Mohammadi et al 2018;Numonov et al 2018). In Western North Iran, the essential oil from roots of P. ferulacea has been traditionally used for wound healing (Yousefi et al 2017).…”
Section: Traditional Use Of Prangos Speciesmentioning
confidence: 99%